Iodination of CART(61-102) peptide: Preserved binding and anorexigenic activity in mice - Pražienková, Veronika; Marek, Aleš; Maletínská, Lenka (Journal of labelled compounds & radiopharmaceuticals, 2021)
CART (cocaine- and amphetamine-regulated transcript) peptides are involved in food intake regulation, stress, and other physiological functions. Although CART peptides have been known for over 25 years, their receptor(s) have not yet been characterized. In this short review, we will summarize our previous studies, where we reported specific binding of 125 I-CART(61-102) to PC12 rat pheochromocytoma cells. Competitive binding experiments performed with mono- and di-iodinated peptides and their isoforms with oxidized Met67 resulted in nanomolar binding affinity. Moreover, in our previous study, CART(61-102), as well as di-iodinated CART(61-102), have shown a strong anorexigenic effect in fasted lean mice after intracerebroventricular administration. In conclusion, from our previous studies, iodination of CART(61-102) resulted in mono- and di-iodinated analogs with or without oxidized Met67 . All analogs revealed a high affinity to binding sites at PC12 cells and preserved biological activity.
Keywords: PC12 Cells; Animals; competitive binding experiments; vazba proteinů; radiofarmaka; anorektika; Cocaine- and Amphetamine-Regulated Transcript Protein; food intake; Mice; myši; proteiny nervové tkáně; PC12 cells; Appetite Depressants; Nerve Tissue Proteins; CART peptide; buňky PC12; krysa rodu Rattus; Radiopharmaceuticals; zvířata; kokainem a amfetaminem regulovaný transkript; Iodine Radioisotopes; Protein Binding; Rats; radioizotopy jodu